Modeling total predation to avoid perverse outcomes from cat control in a data‐poor island ecosystem. Issue 5 (24th August 2022) - Plein, Michaela; O'Brien, Katherine R.; Holden, Matthew H.; Adams, Matthew P.; Baker, Christopher M.; Bean, Nigel G.; Sisson, Scott A.; Bode, Michael; Mengersen, Kerrie L.; McDonald‐Madden, Eve
Abstract: Data‐hungry, complex ecosystem models are often used to predict the consequences of threatened species management, including perverse outcomes. Unfortunately, this approach is impractical in the many systems that have insufficient data to parameterize ecosystem interactions or reliably calibrate or validate such models. We devised a different approach composed of a minimum realistic model that guides decisions in data‐ and resource‐scarce systems. We applied our approach to a case study in an invaded ecosystem from Christmas Island, Australia, where there are concerns that cat ( Felis catus ) eradication to protect native species, including the red‐tailed tropicbird ( Phaethon rubricauda ), could release mesopredation by invasive rats ( Rattus rattus ). We used biophysical constraints (metabolic demand) and observable parameters (e.g., prey preferences) to identify the combined cat and rat abundances that could threaten the tropicbird population. The population of tropicbirds was not sustained when predated by 1607 rats (95% credible interval [CI]: 103–5910) in the absence of cats and 21 cats (95% CI: 2–82) in the absence of rats. For every cat removed from the island, the bird's net population growth rate improved, provided rats did not increase by more than 77 individuals (95% CI: 30–174). Thus, in this context, 1 cat is equivalent to 30–174 rats. Our methods are especially useful for on‐the‐ground predator control in the absence of knowledge of predator–predator interactions to determine whether current abundance of predators threatened the prey population of interest; managing only 1 predator species was sufficient to protect the prey species given potential release of another predator; and control of multiple predator species was needed to meet the conservation goal. With our approach limited information can be used for maximum value in data‐poor systems because it shifts the focus from predicting future trajectories to identifying conditions that impede conservation. Resumen: Los modelos ambientales complejos y con un gran volumen de datos se usan con frecuencia para pronosticar las consecuencias de la gestión de las especies amenazadas, incluyendo los resultados perversos. Desafortunadamente, esta estrategia no es práctica en los tantos sistemas que no tienen suficientes datos para formular un parámetro de las interacciones en el ecosistema o calibrar o validar con confianza dichos modelos. Diseñamos una estrategia diferente compuesta de un modelo realista mínimo que orienta las decisiones dentro de los sistemas con escasez de datos y recursos. Aplicamos nuestra estrategia a un estudio de caso en un ecosistema invadido de la Isla Navidad, Australia, en donde existe preocupación por la eliminación del gato doméstico ( Felis catus ) para proteger a las especies nativas, incluida el ave tropical de cola roja ( Phaethon rubricauda ), como posible impulsor de la mesodepredación por ratas invasoras ( Rattus rattus ). Usamos restricciones biofísicas (demanda metabólica) y parámetros observables (p. ej.: preferencia por presas) para identificar la abundancia combinada de gatos y ratas que podrían amenazar a la población de Phaethon rubricauda . La población de esta especie no fue constante cuando fue presa de 1607 ratas (95% intervalo de credibilidad [IC] 103–5910) en ausencia de gatos y cuando fue presa de 21 gatos (95% IC 2–82) en ausencia de ratas. Por cada gato que se eliminó de la isla, la tasa neta de crecimiento poblacional de la especie aumentó, bajo la condición de que las ratas no incrementaran en más de 77 individuos (95% IC 30‐174]). Por lo tanto, dentro de este contexto, 1 gato es equivalente a 30–174 ratas. Nuestros métodos son realmente útiles para el control in situ de depredadores en ausencia de información sobre las interacciones depredador‐depredador para determinar si la abundancia actual de depredadores amenaza a la población presa de interés. La gestión de 1 especie depredadora fue suficiente para proteger a la especie presa bajo la potencial liberación de otro depredador y se necesitó del control de varias especies depredadores para lograr el objetivo de conservación. Con nuestra estrategia, la información limitada puede usarse para el valor máximo en los sistemas deficientes de información ya que cambia el enfoque de la predicción de futuras trayectorias a la identificación de las condiciones que impiden la conservación. 在数据匮乏的岛屿生态系统中构建总捕食量模型以避免对猫的数量管理导致不当结果: 【摘要】 需要大量数据的复杂生态系统模型经常被用于预测管理受威胁物种的结果, 包括反常结果。然而, 这种方法在许多系统中是不切实际的, 因为这些系统没有足够的数据来对确定生态系统互作的参数, 或是可靠地校准或验证这些模型。我们设计了一种由最小现实模型组成的新方法, 可以在数据和资源缺乏的系统中指导决策。我们将该方法应用于澳大利亚圣诞岛遭受生物入侵的生态系统的案例研究中, 当地为保护原生物种(包括红尾热带鸟[ Phaethon rubricauda ])而消灭猫( Felis catus )的举措可能会放松对入侵的中等捕食者老鼠( Rattus rattus )的压力, 引发了人们的担忧。我们使用生物物理限制(代谢需求)和可观测参数(如猎物偏好)确定了可能威胁到热带鸟种群的猫和鼠的综合丰度。在没有猫的情况下, 热带鸟会被1607只老鼠(95%置信区间[CI] 103‐5910)捕食, 而在没有老鼠的情况下, 会被21只猫(95% CI 2‐82)捕食, 种群都无法维持。每从岛上移除一只猫, 只要老鼠不增加超过77只(95% CI 30‐174), 鸟类的净增长速度就会提高。因此, 在这种情况下, 1只猫相当于30‐174只老鼠。我们的方法特别适用于以下情况:在不了解捕食者互作的情况下进行实地捕食者控制, 以确定当前的捕食者丰度是否会威胁到关注的被捕食者种群;考虑到对另一种捕食者潜在的捕食压力放松, 只管理一种捕食者就足以保护被捕食者物种;需要控制多种捕食者以达到保护目标。我们的方法将重点从预测未来轨迹转移到识别阻碍保护的条件, 因此可以在数据缺乏的系统中将有限的信息可以发挥最大价值。【翻译:胡怡思;审校:聂永刚】